Artificial Intelligence and Planning Decision-making for Volunteer Work Programs at Princess Nourah Bint Abdul Rahman University to achieve the Kingdom's 2030 Vision - Hessa Alsanad (Journal of Umm Al-Qura University for Social Sciences, 2021)
This study aims to determine the relationship between artificial intelligence and planning decision-making for volunteer work programs at Princess Nourah Bint Abdul Rahman University to achieve the Kingdom's 2030 vision. It was applied to a simple random sample of (532) by (322) participant from female faculty members and assistance them. Else, a sample of (210) participant from female supervisors from the colleges and the Deanship of Student Affairs at the university. The study reached a number of results, the most prominent of were: "The presence of a positive correlation with statistically significant between artificial intelligence and planning decision-making for volunteer work programs at the university to achieve the Kingdom's vision 2030, at a level of significance 0.01 for the Pearson correlation coefficient with a statistical significance ."(.000)